Promoting HPV Prevention in the School Setting. (March 2013) - Bellia-Weiss, Tania; Parsons, Mary; Sebach, Aaron M.; Rockelli, Laurie A.
In pediatrics especially, it is important to incorporate the latest immunization and Healthy People 2020 guidelines while working to promote health and prevent disease in children. Human papillomavirus (HPV) is the most common sexually transmitted infection in the United States with at least 20 million people infected. Consequently, approximately 18, 000 women and 7, 000 men are diagnosed with HPV associated cancers yearly. Gardasil is a quadrivalent vaccine that protects against HPV strains 6, 11, 16, and 18. It is currently recommended by the Advisory Committee on Immunization Practices for both males and females between 11 and 26 years of age. HPV immunization rates are lower than the intended 80% goal of Healthy People 2020, with only 26.7% of the population having completed the vaccination series. Focused, timely, and persistent education and prevention efforts are needed in school settings to increase vaccination rates and decrease HPV morbidity.